Preliminary Study: Blockchain and Its Challenge in the Construction Industry - Rosli, Muhammad Ariff Najmie; Che Haron, Roziha (Research in Management of Technology and Business, 2024)
Despite the growing complexity of construction projects, stemming from diverse disciplines, the risk of human error and delay continues to escalate. To gain a competitive advantage, Malaysia's construction industry needs to develop new organizational and efficiency tools. The Construction 4.0 Strategic Plan identifies 12 disruptive technologies, including blockchain, which is a key area for advancement. Blockchain is a decentralized ledger technology that secures, verifies, and maintains transactions on a peer-to-peer network. Despite blockchain's potential benefits for the construction industry and its status as a disruptive innovation, its adoption rate has not met market expectations. This is due to the lack of understanding and support for blockchain technology, as well as the absence of transparent laws and regulations, contribute to the slow adoption. In addition, the high investment costs and slow stakeholder receptivity also hinder the full adoption of blockchain in the construction industry. Therefore, the purpose of this study is to provide a preliminary understanding of blockchain technology and its challenges in adoption for the construction industry.